1984
DOI: 10.1084/jem.160.4.1247
|View full text |Cite
|
Sign up to set email alerts
|

Defective membrane potential changes in neutrophils from human neonates.

Abstract: DEFECTIVE MEMBRANE POTENTIAL CHANGES IN NEUTROPHILS FROM HUMAN NEONATESBe FULVIO SACCHI AND HARRY R. HILLA number of studies have been carried out to determine the functional activity of polymorphonuclear leukocytes (PMN) from human neonates in an attempt to explain their unusual susceptibility to infection. Although neonatal PMN are capable of ingesting and killing microorganisms (1, 2), chemotaxis of these cells is markedly impaired in vitro and in vivo (3-7). The mechanism(s) involved in the pathogenesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

1987
1987
1994
1994

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 16 publications
2
26
1
Order By: Relevance
“…This may explain our results if up-regulation is critical for the PMN response, which is not in agreement with other results previously reported (31). Other altered stimulus-response coupling mechanisms in N-PMN, such as the changes in membrane potential after chemotactic stimulation (32), could play a role in the low STZstimulated LTB, production.…”
Section: Discussioncontrasting
confidence: 50%
“…This may explain our results if up-regulation is critical for the PMN response, which is not in agreement with other results previously reported (31). Other altered stimulus-response coupling mechanisms in N-PMN, such as the changes in membrane potential after chemotactic stimulation (32), could play a role in the low STZstimulated LTB, production.…”
Section: Discussioncontrasting
confidence: 50%
“…Strauss and Snyder (74) also reported employing the potential sensitive dye DiOC5(3). We (23) found that the binding of FMLP to PMNs from neonates was normal that the PMNs of neonates with defective chemotactic function at both 22 and 4" C, and that the affinity of the binding was failed to show the hyperpolarization response observed following normal at both temperatures. Based on the results of their studies, chemotactic factor stimulation of PMNs from adults (Fig.…”
Section: Abnormalities In Neonatal Polymorphonuclear Leukocytesmentioning
confidence: 89%
“…Employing the low levels of this critical energy source (81). Thus, both an calcium-sensitive probe Quin 2/AM, we (23) found that the level of free calcium reached within the PMNs of neonates was lower 40 than that of the PMNs from adults following chemotactic factor stimulation (Fig. 2).…”
Section: Abnormalities In Neonatal Polymorphonuclear Leukocytesmentioning
confidence: 97%
See 1 more Smart Citation
“…The normal increase in intracellular free calcium concentration that occurs upon stimulation of adult PMNs with f-MLP is also reduced in newborns' PMNs. (3). In addition, phagocytosis by neonatal cells has been shown to be deficient when limiting amounts of serum were used for opsonization of the test organisms (5,6).…”
mentioning
confidence: 99%